DAMPAK MULTIBAHAYA ROB DAN EROSI PANTAI PADA PERUBAHAN NILAI MANFAAT SOSIAL DAN EKONOMI HUTAN MANGROVE DAN LAHAN TAMBAK DI WILAYAH KEPESISIRAN KABUPATEN DEMAK (Kasus: Kecamatan Sayung, Kecamatan Karangtengah, Kecamatan Bonang) - , DANA ADISUKMA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Multihazards phenomena of rob and coastal erosion in Demak Coastal Area was impacted to the fishpond and mangrove ecosystem uses in particularly on socio-economic aspects. The aim of this research are consist of to compose the multihazard map of rob and coastal erosion, to predict the economic and social values of mangrove and fishopond uses and to describe the correlation of economic impact with social impact by multihazards. The sampling method in this research is purposive sampling. The analysis method for economic value of mangrove ecosystem is using indirect value approach with biological, salt water intrution defense, and phisical components. The analysis of economic value of fishpond are consist of two main variable, productivity and feasibility. The productivity variable are consist of profit and rentability components. The feasibility variable are consist of NPV, Net- BCR, IRR and Payback Period Values. The analysis method for social values is descriptive method. The analysis method for impact correlation of multihazard is Kendallâs Tau of parametric quantitative statistics. The result of the multihazard map is devided into high, middle, low and none level. The economic and social values change of mangrove and fishpond uses are affected by multihazards level of rob and coastal erosion. The correlation between social and economic impacts of multihazard is on low correlation and high affected. Keywords: Multihazard, rob, coastal erosion, social and economic values, mangrove ecosystem, fishpond